Effect of plot size and precipitation magnitudes on the activation of soil erosion processes using simulated rainfall experiments in vineyards - Neumann, Martin; Kavka, Petr; Devátý, Jan; Stašek, Jakub; Strouhal, Luděk; Tejkl, Adam; Kubínová, Romana; Rodrigo-Comino, Jesús (Frontiers in Environmental Science, 2022)
Soil erosion is recognized as a threat to humankind and natural ecosystems when sustainable limits are exceeded. For decades, various researchers have used various tools to assess combinations of extreme rainfall events and non-sustainable soil management practices, and have developed tools, e.g. rainfall simulators, aimed at activating runoff and at drastically reducing soil loss. However, the idea of assessing combinations of extreme rainfall events and soil management practices using two different devices of different sizes has not been tested before. The aim is to verify whether plot size, connectivity processes and rainfall distribution affect the activation of soil erosion. In this research on soils cultivated with vineyards in the Moravia Region in the south-east part of the Czech Republic, we have performed various rainfall simulation experiments with a small device (1x1 m) and with a large device (8x1 m). Our results show that the surface runoff was approximately 30% higher on the small plot than on the large plot. The large rainfall simulator produced a sediment concentration that was up to 3 times higher, and a soil loss that was up to 1,5 times higher, even when the surface runoff was 30-50 % lower for the large rainfall simulator. We, therefore, conclude that there is a clear influence of surface length and plot size on the surface runoff, soil loss and sediment concentration activation. When planning their experiments, researchers need to take into account that the type of device can have a drastic influence on the final results. Two devices subjected to the same rainfall intensity (60 mm h-1) can produce very different results, e.g. depending on plot size and kinetic energy.